2009
DOI: 10.2337/dc09-0130
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Pragmatic Education Program Designed to Promote Walking Activity in Individuals With Impaired Glucose Tolerance

Abstract: OBJECTIVETo investigate whether a pragmatic structured education program with and without pedometer use is effective for promoting physical activity and improving glucose tolerance in those with impaired glucose tolerance (IGT).RESEARCH DESIGN AND METHODSOverweight and obese individuals with IGT were recruited from ongoing screening studies at the University Hospitals of Leicester, U.K. Participants were randomly assigned to one of three groups. Group 1 received a 3-h group-based structured education program d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
264
5
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(278 citation statements)
references
References 23 publications
4
264
5
3
Order By: Relevance
“…Indeed, the efficacy of lifestyle modification programs to improve the cardiometabolic risk profile has already been well documented (20)(21)(22)(23)(24). Instead, the present study was designed to test whether a 1-year healthy eating-physical activity/exercise program in viscerally obese men would change the cardiometabolic risk profile through VAT and/or SAT reduction and whether changes in VAT would be related either to changes in global adiposity or to changes in cardiorespiratory fitness or to both.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the efficacy of lifestyle modification programs to improve the cardiometabolic risk profile has already been well documented (20)(21)(22)(23)(24). Instead, the present study was designed to test whether a 1-year healthy eating-physical activity/exercise program in viscerally obese men would change the cardiometabolic risk profile through VAT and/or SAT reduction and whether changes in VAT would be related either to changes in global adiposity or to changes in cardiorespiratory fitness or to both.…”
Section: Discussionmentioning
confidence: 99%
“…The curriculum was informed by previous prevention programmes that our research group has developed. [240][241][242] Additional qualitative work was undertaken to further inform the content, process and style of delivery.…”
Section: Overview Of the Development Processmentioning
confidence: 99%
“…[240][241][242] In addition, abstract concepts such as risk and future self were to be developed as activities, games or stories using a concrete kinaesthetic modality. To promote participant engagement in the programme, the educators would use practical and participatory methods, such as food models and images, visual memory aids and short walks using a pedometer.…”
Section: Curriculum Content and Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The research into the effects in CKD and DM remain unclear and the Cochrane review found no improvement in fasting plasma glucose, fasting plasma insulin or glucose disappearance. However Yates [23] et al did show improvements in glucose control in overweight or obese diabetic patients after 12 months of an exercise intervention, which suggests that if positive results can be achieved in patients with DM, further work is required to analyse the effects in those patients with CKD secondary to DM.…”
Section: What Are the Health Benefits Of Exercise In Ckd?mentioning
confidence: 99%